Regional Policy, Economic Growth and Convergence Lessons from the Spanish Case - Cuadrado-Roura, Juan R. (Springer Berlin Heidelberg, 2010)
Many European, Latin American and Asian countries have experience with regional policies aiming to reduce regional disparities in GDP per capita and/or to develop problem regions helping to recover from its GDP decrease. Spain represents, without any doubt, a very rich and interesting case-study regarding regional problems and regional development policies. The aim of this book is not only to analyze the regional policies practiced, their objectives, instruments and effects, but to provide an in-depth analysis on the impact of investments in infrastructure, human capital and other factors, as well as the advances accomplished in terms of productivity, convergence and regional competitiveness. The book particularly wants to impart knowledge, which can be useful for other countries policy makers, as well as for academics, researchers and consultants. The contributions selected have been written by prestigious Spanish academics, most of them also having practical experience in the field.